HAK ASASI MANUSIA SEBAGAI BAROMETER HUKUM DAN GLOBALISASI - Suprijatna, Dadang (DERECHTSSTAAT, 2017)
Human rights as a barometer of the law in its formation is to see from the social phenomena that grow and develop in society that gave birth to social contract. Society is understood as the unity of separate individuals who build a personal bond before the emergence of society itself. The states form of responsibility to its people is to create opportunities for people to gain their rights, as a form of contribution to the people as legitimate owners. The State can no longer ignore any form of any popular will, it is a Right that must be protected and gained great influence from other societies, including the international community globally, which can ultimately affect and / or become a barometer of globalization. Globalization is portrayed as increasing interconnection and social interdependence, politics, economy, law and culture of society behavior, but globalization has also resulted in diminishing the virtue of nation state even an important phenomenon that can not be avoided by anyone, any nation and any country, including Society, nation and state of Indonesia. For that it is fitting for the people and the Indonesian nation to be wary of the growth and development of Globalization that can damage the Mission of Pancasila as the Reject Measure the life of nation and state.